Why do foreign banks withdraw from other countries? A panel data analysis - Aneta Hryckiewicz; Oskar Kowalewski (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper describes the trends in foreign bank ownership across the world and presents, for the first time, empirical evidence of the causes of multinational banks' exits from other countries. Using panel data for 149 closed or divested foreign bank subsidiaries across 54 countries from 1997 to 2009, we show that the problems encountered by subsidiaries were not the main cause of divestment by parent banks. Based on data for the parent banks of the closed subsidiaries, our results show that those parent banks reported significant financial weaknesses prior to closing their international operations. Therefore, we assume that a multinational bank's decision to close or sell a subsidiary in another country is based mainly on problems in the home country, with a lesser factor being the weak performance of the foreign subsidiary.
Keywords: G21; G34; F20; 330; foreign banks; subsidiary; divestment; performance; Internationale Bank; Auslandsniederlassung; Desinvestition; Unternehmensentwicklung; Schätzung; Welt